Kreativitas Pegawai Sebagai Modal Adaptif dalam Perubahan Organisasi: Studi Kasus DPMPTSP Kabupaten Takalar, Sulawesi Selatan - Henri Henri; Nasir Nasir (Universitas Methodist Indonesia, 2026)
Organizational change in government institutions requires employees who are adaptive and creative so that public services remain effective and responsive. Prior studies on employee creativity in the public sector have largely been descriptive and quantitative at a general level, with limited attention to how creativity is actually enacted within a one-stop licensing service undergoing digital transformation. This study addresses that gap by examining how employee creativity manifests during organizational change at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Takalar Regency, South Sulawesi, Indonesia. A qualitative case study approach was used, drawing on 12 purposively selected informants (structural officials and frontline staff) through semi-structured interviews, non-participant observation, and document review; data were analyzed using an interactive model (data reduction, data display, and conclusion drawing) with source and method triangulation to establish credibility. The findings show that employee creativity is expressed through four recurring practices: work-process innovation, adoption of digital technology, simplification of service procedures, and initiative in problem-solving, while its distribution remains uneven across work units because of individual risk aversion and inconsistent managerial support. This study contributes a contextual model linking leadership openness, gaps in the reward system, and the enactment of creativity in local e-government service delivery, offering practical guidance for strengthening an innovation culture in comparable public agencies.